2004
DOI: 10.1152/ajpheart.01135.2003
|View full text |Cite
|
Sign up to set email alerts
|

ANG II signaling in vasa recta pericytes by PKC and reactive oxygen species

Abstract: ANG II constricts descending vasa recta (DVR) through Ca(2+) signaling in pericytes. We examined the role of PKC DVR pericytes isolated from the rat renal outer medulla. The PKC blocker staurosporine (10 microM) eliminated ANG II (10 nM)-induced vasoconstriction, inhibited pericyte cytoplasmic Ca(2+) concentration ([Ca(2+)](cyt)) elevation, and blocked Mn(2+) influx into the cytoplasm. Activation of PKC by either 1,2-dioctanoyl-sn-glycerol (10 microM) or phorbol 12,13-dibutyrate (PDBu; 1 microM) induced both v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 59 publications
(102 reference statements)
6
31
0
Order By: Relevance
“…Tempol fully prevents the graded vasoconstriction of isolated, perfused Aff to the O 2 ⅐ Ϫ -generating quinolone paraquat (19). Studies with fluorescence indicators of O 2 ⅐ Ϫ have confirmed that tempol, in the dosage used in this study, fully prevents the generation of O 2 ⅐ Ϫ in isolated, perfused vasa recta that are stimulated with AngII (27). This was confirmed in this study, in which enhanced vascular O 2 ⅐ Ϫ generation by NE during ␤ 1 -adrenergic receptor blockade was normalized by bath addition of 10 Ϫ4 M tempol.…”
Section: Discussionsupporting
confidence: 67%
“…Tempol fully prevents the graded vasoconstriction of isolated, perfused Aff to the O 2 ⅐ Ϫ -generating quinolone paraquat (19). Studies with fluorescence indicators of O 2 ⅐ Ϫ have confirmed that tempol, in the dosage used in this study, fully prevents the generation of O 2 ⅐ Ϫ in isolated, perfused vasa recta that are stimulated with AngII (27). This was confirmed in this study, in which enhanced vascular O 2 ⅐ Ϫ generation by NE during ␤ 1 -adrenergic receptor blockade was normalized by bath addition of 10 Ϫ4 M tempol.…”
Section: Discussionsupporting
confidence: 67%
“…In that preparation, AT2R activation increases NO bioavailability by inhibiting generation of reactive oxygen species. 17,19 Taken together, the finding by Gonzales et al 1 that AT2R activation is vasodilatory largely supports previous observations.…”
supporting
confidence: 86%
“…NAD(P)H oxidase, as well as other metabolic oxidases such as xanthine oxidase and mitochondrial respiratory chain enzymes (I-IV), are functional in the kidney (278). However, we and others have identified NAD(P)H oxidase-induced ROS production as a primary initiator of oxidative stress within the kidney (183,353,355,356 onists that bind to D1-like receptors, and to H ϩ fluxes (28,89,146,184,259,353,377,384) (Figs. 6 through 9).…”
Section: Nistala Et Al 2060mentioning
confidence: 91%